2007
DOI: 10.1039/b616616d
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the quenching of core and core-shell CdSe quantum dots by binding and non-binding nitroxides

Abstract: The quenching of core and core-shell CdSe quantum dots by TEMPO and 4-amino-TEMPO has been examined using steady state fluorescence spectroscopy. The efficiency of quenching is strongly dependent on the nanoparticle size, the binding properties of the nitroxide, and the presence or not of a protective shell, ZnS in our systems. The shell reduces the quenching efficiency significantly only in the case of binding nitroxides, such as 4-amino-TEMPO. Downward quenching plots revealing bimodal quenching characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…One of QDs' applications in biosensing methods is fluorescence quenching. As already reported, in aqueous solutions, the fluorescence intensity of QDs could be effectively quenched by heavy metal ions like Pb 2+ [27], Cu 2+ [28][29][30], or free radicals [31,32]. Our preliminary tests indicated that several components or contaminants contained in used oils, such as heavy metal ions, free radicals, electron withdrawing groups, and conjugated carbon-carbon double bonds, could also quench the fluorescence of QDs.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…One of QDs' applications in biosensing methods is fluorescence quenching. As already reported, in aqueous solutions, the fluorescence intensity of QDs could be effectively quenched by heavy metal ions like Pb 2+ [27], Cu 2+ [28][29][30], or free radicals [31,32]. Our preliminary tests indicated that several components or contaminants contained in used oils, such as heavy metal ions, free radicals, electron withdrawing groups, and conjugated carbon-carbon double bonds, could also quench the fluorescence of QDs.…”
Section: Introductionsupporting
confidence: 77%
“…It was reported that free radicals could quench the fluorescence of QD nanoparticles [31], and the quenching of QD luminescence by radicals was non-linear [57,58]. For the quenching of QD luminescence by organic radicals, a mechanism of the ligand exchange of TOPO with radicals was speculated by Heafey et al [32]. Recently a new mechanism was proposed requiring close proximity for electron transfer or spin exchange between the radical (electron acceptor) and the excited electron in the conduction band of QD (electron donor) [59].…”
Section: Comparison Of Oil-soluble Qds and Water-soluble Ctab-coated Qdsmentioning
confidence: 99%
“…A major aim of work in this field is to be able to control the processes that occur between NC excitons and the surrounding environment. Trap states studied in our NC samples may be regarded as a model system for a wide range of reactions that transfer charge out of nanoscale materials and a deep understanding of these processes could potentially drive the application of NCs in photovoltaics (51,52), sensors (53), or other applications that require the controlled interaction of nanoscale excitons.…”
Section: Discussionmentioning
confidence: 99%
“…Other reason may be their lower stability compared QDs with higher hydrodynamic diameter [35]. It was reported, that fluorescence of QDs was quenched due to the residues of polymerization agents ammonium persulfate [36], tetramethylethylenediamine [37] or acrylamide [38]. However, after polymerization of the gels, the free polymer subunits (acrylamide and bisacrylamide) and polymerization catalysers are present in trace concentration and their concentration is lowered by overnight storage of the gels [39].…”
Section: Electrophoretic Separation Of Qdsmentioning
confidence: 99%